El paladio frente a otros activos financieros subyasentes, y cual es su cartera ideal (2019)
In this work we want to know the characteristics and the events in the market, which has obtained an increase of 234% in the price of palladium since 2016 and has increased by almost 50% of the price in this year 2019, knowing its current world situation, its supply and demand factors, as well as the factors that can be seen in its behavior in the market, taking equal or inverse relationships that may exist among other financial assets. Also we are going to do a technical analysis that allows us to know the risk, volatility and trend, to be able to characterize this asset and be able to put in an investment portfolio that fits this type of asset.